Cytokinins Induce Prehaustoria Coordinately with Quinone Signals in the Parasitic Plant Striga hermonthica. (16th September 2022) - Aoki, Natsumi; Cui, Songkui; Yoshida, Satoko
Abstract: Orobanchaceae parasitic plants are major threats to global food security, causing severe agricultural damage worldwide. Parasitic plants derive water and nutrients from their host plants through multicellular organs called haustoria. The formation of a prehaustorium, a primitive haustorial structure, is provoked by host-derived haustorium-inducing factors (HIFs). Quinones, including 2, 6-dimethoxy- p -benzoquinone (DMBQ), are of the most potent HIFs for various species in Orobanchaceae, but except non-photosynthetic holoparasites, Phelipanche and Orobanche spp. Instead, cytokinin (CK) phytohormones were reported to induce prehaustoria in Phelipanche ramosa . However, little is known about whether CKs act as HIFs in the other parasitic species to date. Moreover, the signaling pathways for quinones and CKs in prehaustorium induction are not well understood. This study shows that CKs act as HIFs in the obligate parasite Striga hermonthica but not in the facultative parasite Phtheirospermum japonicum . Using chemical inhibitors and marker gene expression analysis, we demonstrate that CKs activate prehaustorium formation through a CK-specific signaling pathway that overlaps with the quinone HIF pathway at downstream in S. hermonthica . Moreover, host root exudates activated S. hermonthica CK biosynthesis and signaling genes, and DMBQ and CK inhibitors perturbed the prehaustorium-inducing activity of exudates, indicating that host root exudates include CKs. Our study reveals the importance of CKs for prehaustorium formation in obligate parasitic plants.